Thrust and stiffness nomograms for hydrostatic bearing calculations - Cooke, P.; Scarr, A. J. (College of Aeronautics, 1966)
The application of hydrostatic lubrication to slideways is now becoming common practice in the machine tool industry. The theoretical basis for determining design parameters for hydrostatic lubrication is well established (Refs. 1 and 2) but one of the practical problems facing the machine tool designer wishing to use this technique is the tedious computation involved in arriving at suitable design parameters ... [cont.].